SOCIAL DETERMINANTS OF ADHERENCE TO DIETARY AND PHYSICAL ACTIVITY RECOMMENDATIONS AMONG ADULTS WITH OBESITY - A COMPREHENSIVE LITERATURE REVIEW (2010–2025) - Joanna Kaźmierczak,; Anna Mandecka,; Kornela Kotucha-Cyl,; Weronika Komala,; Natalia Guzik,; Joanna Gerlach,; Dorota Plechawska,; Karolina Witek,; Marta Nowocień, (International Journal of Innovative Technologies in Social Science, 2025)
Background: Adherence to dietary and physical activity recommendations is widely recognized as a cornerstone of effective obesity management. Nevertheless, despite extensive global efforts, adherence rates among adults remain persistently low. Recent evidence indicates that non-adherence is not solely the result of individual motivational or behavioral shortcomings but is deeply embedded within the broader framework of social determinants of health (SDH). Understanding how these determinants shape adherence is therefore essential for developing equitable and sustainable obesity interventions.Objective: This evidence-based narrative review aims to synthesize current knowledge on the impact of socioeconomic, cultural, psychosocial, healthcare, and digital factors on adherence to lifestyle recommendations among adults with obesity.Methods: A comprehensive literature search was conducted across PubMed, Scopus, Web of Science, PsycINFO, and CINAHL databases for studies published between 2010 and 2025. Eligible publications included quantitative, qualitative, and conceptual studies examining social determinants influencing adherence to dietary and physical activity guidance. Extracted findings were thematically analyzed and assessed according to the hierarchy of evidence (Levels I–IV).Results: Thirty peer-reviewed studies met the inclusion criteria. Across diverse settings, socioeconomic disadvantage, lower educational attainment, and financial insecurity consistently predicted poor adherence. Cultural norms, obesogenic environments, and neighborhood safety were found to shape opportunities for engaging in healthy behaviors. Psychosocial determinants - particularly social support, mental health status, and exposure to weight stigma- emerged as significant moderators of adherence. Limited access to healthcare and low health literacy were identified as key mediating factors, while digital inequities further widened adherence gaps despite the increasing role of telehealth and mHealth interventions. Conversely, higher social capital, supportive community structures, and equitable access to healthcare and technology facilitated sustained adherence to lifestyle recommendations.Conclusions: Adherence to dietary and physical activity recommendations among adults with obesity is fundamentally shaped by the social, environmental, and structural contexts in which individuals live. Addressing these determinants requires multilevel strategies that combine personalized behavioral counseling with broader policy initiatives aimed at promoting socioeconomic equity, supportive built environments, and digital inclusion. Sustainable obesity management depends not merely on changing individual behavior, but on transforming the social conditions that enable or constrain healthy living.